THE INFLUENCE OF MOTOR ACTIVITY ON THE FORMATION OF STRESS RESISTANCE IN SERVICEMEN WHILE PERFORMING SPECIAL SERVICE AND COMBAT MISSIONS - Holovanova, I.A.; Okhrimenko, I.М.; Sharapova, J.V.; Fedyk, A.O.; Filippov, M.O.; Misheniuk, R.M.; Lyakhova, N.A. (World of Medicine and Biology, 2024)
The article is aimed to investigate the influence of motor activity on the formation of stress resistance in servicemen while performing special service and combat missions. The research involved 123 commissioned officers aged 30–55 who performed tasks in the combat zone (up to 6 months) at headquarters (command posts) in managerial positions. Group A (n = 37) was formed by commissioned officers who regularly engaged in physical exercises, and Group B (n = 86) by commissioned officers who did not adhere to the regimen of motor activity. Methods: bibliosemantic, questionnaire survey, psychoanalytic, statistical. It has been established that all servicemen, without exception, experience stress while performing service and combat missions. Somatic symptoms of stress are inherent in both commissioned officers who regularly exercised and those who did not adhere to the regimen of motor activity. However, the frequency of stress symptoms in commissioned officers of Group B is significantly (p ˂ 0.001) higher than in Group A. The level of stress, assessed by three psychodiagnostic methods, in commissioned officers of Group A after returning from the secondment was significantly lower than in Group B (p < 0.05–0.01). This suggests that regular motor activity while performing service and combat missions can alleviate the negative impact of stressors, it increases the stress resistance of commissioned officers, helps to restore their emotional state, maintain physical and mental health, and, accordingly, improve professional and combat performance.
Keywords: stress; stress resistance; officers; servicemen; motor activity; health